Nurturing research – are we on track? - Doubell, Anton F. (SA Heart Journal, 2017)
The annual South African Heart Congress is a prominent beacon on the South African cardiology landscape. Few of us would deny that it is an event not to be missed. However, should we analyse the reasons why this is an important event we may struggle to reach consensus. It is an opportunity to establish and nurture relationships with colleagues practicing in various parts of our country. More importantly, it is also an opportunity to establish and nurture relationships with colleagues from the rest of Africa and other continents. We have established a track record of attracting many of the international pacesetters in cardiovascular medicine and the congress provides an ideal opportunity to keep abreast of the latest developments in our field, but critics will say that we can gain the same exposure and more by attending international meetings such as the European Society of Cardiology (ESC) Congress. The SA Heart Congress provides a platform that allows industry to build relationship with the clinicians and to introduce them to their products. However, one may argue that there are other mechanisms and opportunities to achieve this, both locally and internationally.